Effectiveness of Silica Fume Eggshell Ash and Lime Use on the Properties of Kaolinitic Clay - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan (Taiwan Association of Engineering and Technology Innovation, 2023)
The study aims to investigate the properties of kaolinitic clay using silica fume, eggshell ash, and lime. The experiment employs varying amounts of silica fume (2%, 4%, and 6%), eggshell ash, lime (3%, 6%, and 9%), and combinations of silica fume, eggshell ash, and lime, which are cured for 1, 7, 14, and 30 days. The investigated properties of the soils include the improvement of Atterberg limits, maximum dry density (MDD), optimum moisture content (OMC), specific gravity, compressive strength, morphology characteristics, and chemical compositions. The results reveal that the optimal application of these materials can be achieved at 6% silica fume, 6% eggshell ash, and 9% lime mixture into the soils and increase the shear strength by as much as 88.74% at 30 days of curing.